Edukasi Pencegahan Anemia dan Gangguan Kesehatan Mental Pada Remaja di Kabupaten Bandung - Iceu Mulyati; Yanyan Mulyani; Meda Yuliani; Fikri Mourly Wahyudi; Wahyu Wahdana (Jurnal Medika: Medika, 2026)
Adolescence is a stage of life characterized by rapid physical, psychological, and intellectual changes, which can be challenging for some teenagers. Menstruation, a primary change marking the onset of puberty, significantly influences psychological changes, including discomfort such as abdominal cramps, fatigue, and mood swings, particularly affecting young women.Approximately 15.5 million Indonesian adolescents experience mental health issues, with anxiety being the most common problem (34.9%). Adolescent girls are more prone to depression (6.7%) and anxiety (28.2%), while boys are more likely to experience hyperactivity (12.3%) and behavioral problems (3.5%).The proposed solution involves providing education through anemia exercises and mental health prevention programs, focusing on anemia prevention and mental health issues among adolescents. Community service activities include physical exercises like anti-anemia aerobics, alongside educational sessions. Pre- and post-tests using questionnaires assessed the outcomes, revealing that education significantly improved adolescents' knowledge. The average pre-test score was 66 (min 40, max 80), rising to 87 post-test (min 50, max 100). The Wilcoxon test result (p=0.000) indicates a positive impact of education on enhancing adolescent knowledge. Thus, educating adolescents remains a viable approach to increasing awareness about anemia prevention and mental health issues.